TECHNICAL AND COST PERFORMANCE OF MICROHYDRO POWER PLANT - Haryanto, Agus; Fauzan, Muhamad Inu; Lanya, Budianto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
The increase in electricity consumption in one side and the depletion of fossil fuel sources in the other side have triggered Indonesia to support any development of renewable-based electricity generation, including microhydro-based power plant. The objective of this research was to investigate technical and cost performance of microhydro power plant. Observation was conducted on four microhydro power plants located in Bogorejo village, Sub district of Gedong Tataan, Pesawaran District, Lampung Province. The plants were developed and self-managed by the community. Parameters to be measured or recorded included head of water, voltage and electrical current produced from the generator, number of family serviced by the plant, and electricity price that community should pay. Results showed that power output of the plants was ranging from 314 to 1805 W with 2 to 20 families were serviced for each unit. The research revealed that output power was related to the combination factor of head, the diameter of base penstock pipe, and inverse of generator’s pulley size. The output power was also linearly related to installation cost. With an installation cost of 8 to 40 million rupiahs per unit, the electric energy price was in the window of 633 to 973 rupiahs per kWh. It was concluded that Rohman’s microhydro, with power output of 1805 W and energy price of Rp.633/kWh, was the best compared to the others. Keywords: microhydro, performance, energy price, power